ACTUALIZATION OF THE VALUE OF SUFISM EDUCATION AND ITS RELEVANCE IN THE LIVES OF STUDENTS IN ISLAMIC BOARDING SCHOOLS MUSTHAFAWIYAH DISTRICTS MANDAILING NATAL - Ahmad Suhaimi, Saiful Akhyar Lubis, Syamsu Nahar (At-Tazakki: Jurnal Kajian Ilmu Pendidikan Islam dan Humaniora, 2019)
Abstract: The problem of this research is how the actualization of the value of Sufism education in the life of the santri in Islamic boarding schools must be a new way for the Mandailing Natal district. This study aims to determine the actualization of the value of Sufism education in the life of the santri and its relevance in the life of the santri. Methodologi this research is field research (empirical), with a qualitative approach with data collection techniques through interviews, both primary and secondary data. in data collection, the methods used are observation, interviews and documentation. to analyze data the researcher used qualitative analysis techniques with data distribution steps, data reduction, and conclusion drawing. This study shows that the actualization of the value of Sufism education in Islamic boarding schools musthafawiyah purbabaru is carried out outside the existing lesson hours, but is applied to special learning, this shows that Sufism no longer shows compulsory lessons in boarding schools as it used to be. As a result, the actualization of the value of Sufism education is not fully developed optimally, this is also caused by a lack of exemplary than the teacher in the school environment. The life of santri in boarding schools has not fully demonstrated the value of Sufism education, this can be seen from the pattern of life and morality of Islamic boarding schools, ranging from low patience, lack of sincerity in doing, unable to live zuhud, eroded wara 'and qona'ah, this is due to the lack of guidance and supervision and the example of the teacher. and the flow of globalization and the development of the times and learning is limited to theory